Alcohol Intake Increases in Adolescent C57BL/6J Mice during Intermittent Cycles of Phase-Delayed, Long-Light Conditions - Gamsby, Joshua J.; Pribish, Abby M.; Stevanovic, Korey D.; Yunus, Amara; Gulick, Danielle (Frontiers in Behavioral Neuroscience, 2017)
Adolescents naturally go to bed and awaken late, but are forced to awaken early for school and work. This leads to ‘social jetlag’, a state of circadian desynchrony (CD), in which internal biological rhythms are out of sync with behavioral rhythms. CD is associated with increased alcohol intake in adults, but has been less well-studied in adolescents. The goal of this study was to model adolescent alcohol intake during similar CD conditions in male C57BL/6J mice. Free access alcohol intake, water intake, and wheel-running activity were measured during a normal 12HR photoperiod or during alternating photoperiod (experiment 1: 12h light for 4 days followed by 18h light for 3 days, with dark (activity onset) delayed 9h during the 18HR photoperiod; experiment 2: 12h light for 4 days followed by 6h light for 3 days, with dark onset delayed 3h during the 6HR photoperiod). In experiment 1, CD produced a small but significant increase in the total alcohol intake per day as well as in intake in bouts, with the greatest increase over controls in the hours following the 6HR dark period. Additionally, the pattern of alcohol intake in bouts shifted to increase alcohol intake during the shorter dark period. In experiment 2, the opposite effect occurred – the longer dark cycle led to lower alcohol drinking in the second half of the dark period. However, in experiment 2, CD produced no significant changes in either total alcohol intake or alcohol intake in bouts. Conclusion: Shifts in the light cycle that disrupt the regular pattern of day and night, and increase the length of the night phase, are sufficient to increase both drinking in bouts and restricted drinking in adolescent mice, modeling increased alcohol intake in adolescents during CD.